ANALISIS KUALITAS PENGAJARAN GURU SEKOLAH DASAR BERDASARKAN PERSPEKTIF SISWA DALAM STUDI KASUS SD KRISTEN MAKEDONIA NGABANG - TAREZE, MARIA APRILINE HEGA; Meisakh Nur Anugrah ,; Afandi,; Indri Astuti, (Jurnal Pendidikan Dasar, 2022)
The formal learning process is a process that involves many factors in determining the best results from that process. The quality of learning is a determining factor of the optimal teaching and learning process so it needs to be considered by all teachers. This study aims to explore the quality of learning for elementary school teachers in Makedonia Christian Elementary School based on the results of the student perceptions. Sample from 34 students at Makedonia Christian Elementary School completed the survey using a questionnaire. This perspective is covered by 5 indicators, namely Class Climate, Class Management, Learning Instructions, learning challenges, and learning objectives. The students' perspective is an efficient way to evaluate their teachers because their views are based on the experiences they get when interacting with objects every day. In addition, by conducting regular evaluations, the quality of learning will also be maintained according to needs and developments. The findings of this study indicate that the quality of learning in Makedonia Christian Elementary School has been running very well (mean = 88.13).